Utilizing TikTok Animation for Nutrition Education: A Feasibility and Preliminary Efficacy Study among Mothers Underweight of Toddlers - Lestari, Dian; Sari, Yulia; Febrinasari, Ratih Puspita (Media Publikasi Cendekia Indonesia, 2025)
Underweight is a condition of body weight based on the toddler's age (BW/A) with a Z-score value <2SD. This study aims to develop TikTok animated videos to help toddlers overcome being underweight. The type of research uses Research and Development (R&D) with the ADDIE model, including Analysis, Design, Development, Implementation, and Evaluation. However, this study is only up to the development stage. Video validation involved three experts, namely material, language, and media experts, with an average result of 80.3 (feasible category, minor revision). Furthermore, trials were carried out on prospective users (n=10) selected by purposive sampling. The results of the product assessment by prospective users were 91.08 (very feasible category, no need to revise). The impact of using the video was measured by a knowledge questionnaire (reliability = 0.743). The results of the knowledge score based on the pretest and posttest on mothers of toddlers obtained an average N-Gain score of 0.84 with a high category. Developing the TikTok animated video product is feasible based on the results of the analysis. It can be applied as educational media to increase the knowledge of mothers of toddlers and overcome the problem of underweight toddlers.